Preoperative cut-off values for body mass index deny patients clinically significant improvements in patient-reported outcomes after total hip arthroplasty. (June 2020) - ; Arnold, Nicholas; Anis, Hiba; Barsoum, Wael K.; Bloomfield, Michael R.; Brooks, Peter J.; Higuera, Carlos A.; Kamath, Atul F.; Klika, Alison; Krebs, Viktor E.; Mesko, Nathan W.; Molloy, Robert M.; et al.
Abstract : Aims: Thresholds for operative eligibility based on body mass index (BMI) alone may restrict patient access to the benefits of arthroplasty. The purpose of this study was to evaluate the relationship between BMI and improvements in patient-reported outcome measures (PROMs), and to determine how many patients would have been denied improvements in PROMs if BMI cut-offs were to be implemented. Methods: A prospective cohort of 3, 449 primary total hip arthroplasties (THAs) performed between 2015 and 2018 were analyzed. The following one-year PROMs were evaluated: hip injury and osteoarthritis outcome score (HOOS) pain, HOOS Physical Function Shortform (PS), University of California, Los Angeles (UCLA) activity, Veterans Rand-12 Physical Component Score (VR-12 PCS), and VR-12 Mental Component Score (VR-12 MCS). Positive predictive values for failure to improve and the number of patients denied surgery in order to avoid a failed improvement were calculated for each PROM at different BMI cut-offs. Results: There was a trend to improved outcomes in terms of pain and function improvements with higher BMI. Patients with BMI ≥ 40 kg/m 2 had median (Q1, Q3) HOOS pain improvements of 58 points (interquartile range (IQR) 41 to 70) and those with BMI 35 to 40 kg/m 2 had median improvements of 55 (IQR 40 to 68). With a BMI cut-off of 30 kg/m 2, 21 patients would have been denied a meaningful improvement in HOOS pain score in order to avoid one failed improvement. At a 35 kg/m 2 cut-off, 18 patients would be denied improvement, at a 40 kg/m 2 cut-off 21 patients would be denied improvement, and at a 45 kg/m 2 cut-off 21 patients would be denied improvement. Similar findings were observed for HOOS-PS, UCLA, and VR-12 scores. Conclusion: Patients with higher BMIs show greater improvements in PROMs. Using BMI alone to determine eligibility criteria did not improve the rate of clinically meaningful improvements. BMI thresholds prevent patients who may benefit the most from surgery from undergoing THA. Surgeons should consider PROMs improvements in determining eligibility for THA while balancing traditional metrics of preoperative risk stratification. Cite this article: Bone Joint J 2020;102-B(6):683–692.